Reduced breast milk feeding subsequent to cosmetic breast augmentation surgery. Issue 6 (6th April 2015) - Roberts, Christine L; Ampt, Amanda J; Algert, Charles S; Sywak, Mark S; Chen, Jian Sheng C
Abstract: Objective: To determine the effect of cosmetic breast augmentation on subsequent infant feeding. Participants, design and setting: Population‐based record linkage study of women giving birth in New South Wales, January 2006 – December 2011. Birth records were linked longitudinally to maternal hospitalisations up to 11 years before birth. Breast augmentation was identified by surgical procedure codes in hospital records. Main outcome measures: Any breast milk feeding at discharge from birth care, and among infants receiving any breast milk, exclusive breast milk feeding. The before‐and‐after effect of breast augmentation was assessed among women who had the surgery between births. Results: Among 378 389 women who gave birth in the study period, 892 (0.2%) had prior breast augmentation. Among women with breast augmentation, 705 (79%) provided any breast milk to their infant at discharge, compared with 89% among women without augmentation. After adjusting for sociodemographic and pregnancy factors, infants of women with breast augmentation were less likely to receive breast milk at discharge than infants of women without augmentation (adjusted relative risk [ARR], 0.90; 95% CI, 0.87–0.93). However, infants receiving breast milk were not more or less likely to receive breast milk exclusively (ARR, 0.99; 95% CI, 0.97–1.01). Women with augmentation surgery between births changed their breastfeeding behaviour (reduced rates), while those with no augmentation or augmentation before both births did not. Conclusions: Reduced rates of breast milk feeding among women who have undergone breast augmentation underscore the importance of identifying, supporting and encouraging women who are vulnerable to a lower likelihood of breastfeeding.